Kedudukan Masyarakat Hukum Adat Dalam Proses Hak Tanggungan Yang Objeknya Bersumber Dari Tanah Ulayat - Madha, I Gde Anriz; Mas Rwa Jayantiari, I Gusti Agung (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p4, 2022)
The purpose of this study is to analyze the position of customary law communities in the process of placing Mortgage Rights on Ulayat Land and legal provisions related to the placement of Mortgage Rights on Customary Law Community Land. This research uses normative legal research with a statutory and conceptual approach. The results of the study show that the process of placing mortgage rights on ulayat land in customary law communities has consequences in the form of obligations as managers and rights obtained in the form of results obtained from these management rights. Upon the placement of management rights, the authority to use it itself arises and land rights can be granted which are the object of the Mortgage Rights.